The canine prostate cancer cell line CHP‐1 shows over‐expression of the co‐chaperone small glutamine‐rich tetratricopeptide repeat‐containing protein α. (14th January 2016) - Azakami, D.; Nakahira, R.; Kato, Y.; Michishita, M.; Kobayashi, M.; Onozawa, E.; Bonkobara, M.; Kobayashi, M.; Takahashi, K.; Watanabe, M.; Ishioka, K.; Sako, T.; et al.
Abstract: Although androgen therapy resistance and poor clinical outcomes are seen in most canine prostate cancer cases, there are only a few tools for analysing canine prostate cancer by using a cell biological approach. Therefore, to evaluate androgen‐independent neoplastic cell growth, a new canine prostate cancer cell line (CHP‐1) was established in this study. CHP‐1 over‐expressed the co‐chaperone small glutamine‐rich tetratricopeptide repeat‐containing protein α (SGTA), which is over‐expressed in human androgen‐independent prostate cancer. The CHP‐1 xenograft also showed SGTA over‐expression. Although CHP‐1 shows poor androgen receptor (AR) signalling upon dihydrotestosterone stimulation, forced expression of AR enabled evaluation of AR signalling. Taken together, these results suggest that CHP‐1 will be a useful model for investigating the pathogenesis of androgen‐dependent and androgen‐independent canine prostate cancer.